Analysis Of The Earned Value Method on the Road and Bridge Preservation Project in Situbondo-Ketapang-Banyuwangi - Javan Agustian Setyagraha; Budi Witjaksana; Hanie Teki Tjendani (Eduvest - Journal of Universal Studies, 2024)
The implementation of the Situbondo – Ketapang – Banyuwangi Road and Bridge Preservation Project experienced changes in the area being worked on, requiring additional design. Issues arose when the overlay asphalt mix work was halted to await test results for Aspal Modiv PG – 70 from the Pusjatan Bandung Road Materials Laboratory, causing a delay in the 40th week by -0.813%. Delays primarily occurred in the AC - WC and AC - BC asphalt work, affecting project performance. A cost and time analysis was necessary to address this issue. The Earned Value Method (EVM) was used to determine the project's duration and cost until initial handover. The study results indicated that the project cost performance with a CPI > 1 was good, but an SPI of 0.983 < 1 indicated delays. The estimated final project cost is Rp 112,439,121,070.91, with an estimated completion time of 453 days, 3 days longer than the planned schedule.